Opportunities for nurses to increase parental health literacy: a discussion paper - Johnston, R.; Fowler, C.; Wilson, V.; Kelly, Michelle (Informa Healthcare, 2015)
Most families can access a range of health information and advice. Information and advice sources often include nurses, the Internet, social media, books, as well as family and friends. While the immediate aim may be to find information, it can also be to assist with parenting skills, solve parenting problems or as part of decision-making processes about their child’s health. These processes are strongly influenced by the parent’s level of health literacy. Health literacy describes a person’s capacity to obtain and utilize health related information. Although there are numerous health literacy definitions all have clearly defined steps. These steps are: obtaining relevant information; then understanding this information; and finally being able to use the information to achieve the expected outcome. Previous research has linked low levels of parental health literacy with poorer child health outcomes. Given this link, increasing health literacy levels would be advantageous for both families and health services. Nurses working with families are in a position to support the family to increase their health literacy through the use of a variety of strategies. This article outlines how health literacy can influence the way parents seek help when they are concerned about child health issues, the relevance of parental health literacy for nurses and suggests some tools that could be used to support the increase of health literacy.